2002
DOI: 10.1176/appi.ajp.159.6.1053
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of CSF Homovanillic Acid in Recently Abstinent Cocaine-Dependent Patients

Abstract: Recently abstinent cocaine-dependent patients may show dysregulation of the central dopaminergic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Three previous studies found a correlation between cocaine craving and concentrations of the dopamine metabolite homovanillic acid (HVA) in either plasma or cerebrospinal fluid of cocaine abusers (Berger et al, 1996;Knoblich et al, 1992;Martin et al, 1989). A fourth study found higher levels of CSF HVA in recently abstinent cocaine-dependant patients as compared to controls, but no correlation between HVA levels and duration of abstinence (Roy et al, 2002). Administration of haloperidol, a dopamine receptor antagonist, reduced cue-induced cocaine craving in abstinent cocaine abusers in one study (Berger et al, 1996), but had a limited effect on subjective effects of cocaine in another (Sherer et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Three previous studies found a correlation between cocaine craving and concentrations of the dopamine metabolite homovanillic acid (HVA) in either plasma or cerebrospinal fluid of cocaine abusers (Berger et al, 1996;Knoblich et al, 1992;Martin et al, 1989). A fourth study found higher levels of CSF HVA in recently abstinent cocaine-dependant patients as compared to controls, but no correlation between HVA levels and duration of abstinence (Roy et al, 2002). Administration of haloperidol, a dopamine receptor antagonist, reduced cue-induced cocaine craving in abstinent cocaine abusers in one study (Berger et al, 1996), but had a limited effect on subjective effects of cocaine in another (Sherer et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Alebouyeh et al (1) demonstrated the expression of human OAT1 and OAT3 in the ependymal epithelium of the choroid plexus facilitating the efflux of neurotransmitter metabolites, especially of VMA from the brain into the cerebrospinal fluid. OAT3 was also noted to be expressed in the blood-brain barrier, where it may be responsible for the elim- (38). This high K m value detected for rOAT3 leaves the question open regarding whether OAT3 contributes to HVA excretion from the brain under physiological conditions in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have failed to find chronic cocaine-induced neurochemical changes (Kleven et al 1988;Yeh and De Souza 1991;, several preclinical studies have shown that chronic cocaine administration decreases D 1 receptor binding sites ), dopamine transporters (Sharpe et al 1991), dopamine uptake in the frontal cortex (Masserano et al 1994), and concentrations of dopamine and its metabolites, both peripherally ) and in the brain Karoum et al 1990Karoum et al , 1994. In humans, reduced dopamine levels in the frontal cortex, and both increases and decreases in number of dopamine transporters have been reported in post mortem studies of chronic cocaine abusers (Hitri et al 1994;Little et al 1996), and a decrease in dopamine terminal activity in the striatum (Wu et al 1997), higher levels of dopamine metabolites (Roy et al 2002), and changes in dopamine receptor binding (Volkow et al 1990) have been observed in vivo in abstinent cocaine abusers.…”
Section: Introductionmentioning
confidence: 99%